2001
DOI: 10.1111/j.1755-0238.2001.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of lactic acid bacteria to produce N-heterocycles causing mousy off-flavour in wine

Abstract: Thirty-four strains of the genera and species representative of the wine lactic acid bacteria (LAB) were screened in an ethanolic grape juice medium for the production of mousy off-flavour as determined by an alkaline test strip sensory method. Most Lactobacillus spp., Oenococcus oeni and Leuconostoc mesenteroides produced mousy off-flavour, whereas Pediococcus spp. were generally incapable of detectable off-flavour formation. To verify these results, selected LAB were tested for the ability to produce the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 20 publications
4
68
0
Order By: Relevance
“…Three main compounds are involved: 2-acetyl-1-pyrroline (ACPY), 2-ethyltetrahydropyridine (ETPY) and 2-acetyltetrahydropyridine (ACTPY) (Lonvaud-Funel, 1999;Costello et al, 2001). The formation of these compounds is mostly associated with heterofermentative LAB, such as O. oeni, some Lactobacillus species and Leuc.…”
Section: Nitrogen Containing Compoundsmentioning
confidence: 99%
“…Three main compounds are involved: 2-acetyl-1-pyrroline (ACPY), 2-ethyltetrahydropyridine (ETPY) and 2-acetyltetrahydropyridine (ACTPY) (Lonvaud-Funel, 1999;Costello et al, 2001). The formation of these compounds is mostly associated with heterofermentative LAB, such as O. oeni, some Lactobacillus species and Leuc.…”
Section: Nitrogen Containing Compoundsmentioning
confidence: 99%
“…In rice the nitrogen in the pyrroline ring of proline becomes the nitrogen in the pyrroline ring of 2AP while the carboxyl group of proline is removed and replaced with an acetyl group from another source (Yoshihashi et al 2002b). Costello et al (2001) found that in L. hilgardii the acetyl group of 2AP can be derived from fructose when either ethanol or acetaldehyde are supplied in excess. They further suggested D 1 pyrroline, a product of proline catabolism via putrescine oxidation, is the immediate precursor of the pyrroline ring of 2AP and the acetyl group was most likely formed from reaction with acetyl-CoA or acetaldehyde in either a chemical or enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being the major chemical component of fragrance in rice (Buttery et al 1983a), 2AP is a significant aroma chemical in a number of organisms and foodstuffs including Pandanus (Buttery et al 1983b;Laohakunjit and Noomhorm 2004;Thimmaraju et al 2005), popcorn (Schieberle 1995), corn tortillas (Buttery and Ling 1995), baguettes (Zehentbauer and Grosch 1998), ham (Carrapiso et al 2002), cheese (Zehentbauer and Reineccius 2002), mung bean (Brahmachary and Ghosh 2002), green tea (Kumazawa and Masuda 2002), bread flowers (Vallaris glabra Ktze) (Wongpornchai et al 2003) some yeasts (Snowdon et al 2006) and select bacteria (Romanczyk et al 1995;Costello et al 2001;Rungsardthong and Noomhoom 2005;Snowdon et al 2006;Adams and De Kimpe 2007) including the wine spoilage bacteria Lactobaccillus hilgardii (Costello et al 2001;Snowdon et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, strains of Lactobacillus brevis have been frequently isolated from must and wine [3]- [5]. They are spoiling microorganisms due to their ability to produce biogenic amines [5]- [7], ethyl carbamate [6], volatile phenols [8] and mousy off-flavors [9].…”
mentioning
confidence: 99%